Plant-derived natural products targeting inflammation in treatment of atherosclerosis - Hua, Zhen; Wang, Xiaojie; Qin, Le-Le; Zhu, Kun-Peng; Li, De-Ye; Zhang, Xin-Yue; Zhang, Lei; Zhai, Feng-Ting (Frontiers in Pharmacology, 2025)
Atherosclerosis (AS) is a complex and chronic inflammatory vascular disease, and it's also the pathological basis of various diseases such as coronary heart disease. Owing to their advantages such as multiple targets and rich diversity, Plant-Derived natural products with abundant resources will become an important source of anti-AS drugs. Herein, we explored the intricate association between inflammation and AS, focusing on plant-derived natural products that specifically target inflammation for the treatment of AS. This review systematically analyzes 10 plant species, focusing on 23 high-potential metabolites including Tanshinone IIA, Berberine, and Ginsenoside Rb1 et al. We found that natural products with anti-AS properties are primarily derived from plants belonging to the families Araliaceae, Umbelliferae, Fabaceae, and Lamiaceae. The chemical structures of these natural products mainly consist of flavonoids, alkaloids, saponins, and polysaccharides, among others. This suggests that natural products with different structural types can exhibit anti-AS activities, with flavonoids, alkaloids, and saponins showing greater potential. Major anti-inflammatory pathways center on NF-κB/NLRP3 inflammasome inhibition (e.g., Tan IIA, Salidroside), ROS scavenging (e.g., Danshensu, Rosmarinic acid), and endothelial protection (e.g., Astragaloside, Puerarin), while highlighting NLRP3 inflammasome inhibition and gut-microbiota modulation as emerging therapeutic avenues. These will actively promote the clinical application and industrial production of Plant Derived natural products, thereby developing anti AS drugs with excellent efficacy and reduced adverse reactions. We hope that this comprehensive review will provide valuable insights into the potential and pharmacological mechanisms of current natural medicines, thereby offering support for future drug discoveries.